An efficient and simple methodology for the synthesis of 2-amino-4-(N-alkyl/arylamino)-6-chloropyrimidines. Issue 10 (4th March 2015) - Khan, Khalid Mohammed; Iqbal, Sarosh; Bashir, Muhammad Arslan; Ambreen, Nida; Perveen, Shahnaz; Voelter, Wolfgang
Graphical abstract: (a) NaOMe, MeOH, reflux, (b) POCl3, N, N -dimethylaniline, 60 °C, (c) Et3 N, H2 NR/Ar, fusion. Abstract: In this study, twenty-nine 2-aminopyrimidine derivatives are synthesized in good to excellent yields by fusing 2-amino-4, 6-dichloropyrimidine with different amines in the presence of triethylamine without using any solvent or catalyst. Nucleophilic substitution reactions of 2-amino-4, 6-dichloropyrimidine with amines have also been performed in ethanol. Comparisons of the yields and reaction times for both solvent and solvent-free conditions have shown that the newly developed solvent-free protocol is high yielding, more efficient, and simpler compared to conventional methods.